Functional role of delta and theta band oscillations for auditory feedback processing during vocal pitch motor control - Behroozmand, Roozbeh; Ibrahim, Nadine; Korzyukov, Oleg; Robin, Donald A.; Larson, Charles R. (Frontiers in Neuroscience, 2015)
The answer to the question of how the brain incorporates sensory feedback and links it with motor function to achieve goal-directed movement during vocalization remains unclear. We investigated the mechanisms of voice pitch motor control by examining the spectro-temporal dynamics of EEG signals when non-musicians (NM), relative pitch (RP) and absolute pitch (AP) musicians maintained vocalizations of a vowel sound and received randomized ±100 cents pitch-shift stimuli in their auditory feedback. We identified a phase-synchronized (evoked) fronto-central activation within the theta band (5-8 Hz) that temporally overlapped with compensatory vocal responses to pitch-shifted auditory feedback and was significantly stronger in RP and AP musicians compared with non-musicians. A second component involved a non-phase-synchronized (induced) frontal activation within the delta band (1-4 Hz) that emerged at approximately 1 second after the stimulus onset. The delta activation was significantly stronger in the NM compared with RP and AP groups and correlated with the pitch rebound error (PRE), indicating the degree to which subjects failed to re-adjust their voice pitch to baseline after the stimulus offset. We propose that the evoked theta is a neurophysiological marker of enhanced pitch processing in musicians and reflects mechanisms by which humans incorporate auditory feedback to control their voice pitch. We also suggest that the delta activation reflects adaptive neural processes by which vocal production errors are monitored and used to update the state of sensory-motor networks for driving subsequent vocal behaviors. This notion is corroborated by our findings showing that larger PREs were associated with greater delta band activity in the NM compared with RP and AP groups. These findings provide new insights into the neural mechanisms of auditory feedback processing for vocal pitch motor control.